2022
DOI: 10.3389/fnut.2022.901342
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Recent Advances in Rapid Assessment of Anthocyanins in Agricultural and Food Products

Abstract: Anthocyanins (ACNs) are plant polyphenols that have received increased attention recently mainly due to their potential health benefits and applications as functional food ingredients. This has also created an interest in the development and validation of several non-destructive techniques of ACN assessments in several food samples. Non-destructive and conventional techniques play an important role in the assessment of ACNs in agricultural and food products. Although conventional methods appear to be more accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 115 publications
0
17
0
Order By: Relevance
“…Extracting bioactive components from saffron necessitates ongoing research into environmentally and economically viable extraction strategies ( 38 , 39 ). Traditional extraction procedures are time-consuming and necessitate a large amount of solvent ( 40 ).…”
Section: Extraction Of Crocin By Conventional Methods and Novel Techn...mentioning
confidence: 99%
“…Extracting bioactive components from saffron necessitates ongoing research into environmentally and economically viable extraction strategies ( 38 , 39 ). Traditional extraction procedures are time-consuming and necessitate a large amount of solvent ( 40 ).…”
Section: Extraction Of Crocin By Conventional Methods and Novel Techn...mentioning
confidence: 99%
“…Certain foods subjected to heat treatment have the potential to exhibit an increased total phenolic content [102]. There is a possibility that the drying processes that hasten the breakdown of cellular components are to blame for the rise in the total phenol concentration in samples that have been dried [103][104][105][106]. It is possible that the rise can be attributed to the heat-induced breakdown of complex phenolic tannins, which leads to an increased amount of phenolics being extracted [107].…”
Section: Changes In a Structure After Dehydration Of Food Substancementioning
confidence: 99%
“…Nearly 8,000 plant species with medical values have been reported in South Asia, out of which 1,000 exists in Pakistan. With their indigenous knowledge, such plants were used to treat certain diseases for years ( 3 , 4 ). However, modern research reported phytochemicals such as alkaloids, glycosides, saponins, resins, and essential oils with other functional compounds such as furanocoumarins and hydroxycoumarins napthoquinones and acylphloroglucinols in these species.…”
Section: Introductionmentioning
confidence: 99%